Coordination of Regional Disaster Management Agency (BPBD) Tangerang City in Flood Mitigation - Inneka, Tito; Aditya, Toddy (Journal of Government and Civil Society, 2018)
Flooding is a threatening problem both in the city and in the countryside. One of the flood-prone cities is Tangerang City. The cause of flooding is overflowing from the Kali and blockage of existing drainage. Various efforts have been made to prevent flood disasters, the Badan Penanggulangan Bencana Daearah (BPBD) of Tangerang City which is an agency that has the task to assist the disaster, in coordination with the Tangerang City government in order to overcome the problems of frequent floods. The purpose of this study is to analyze how the coordination of Badan Penanggulangan Bencana Daerah (BPBD) in flood prevention in Tangerang City. The research method used is qualitative research. The results of the study show that the coordination of the Regional Disaster Management Agency (BPBD) is well underway and in accordance with the managerial hierarchy, rules and procedures, and plans and goal setting.